Pengaruh Fear of Missing Out dan Electronic Word of Mouth terhadap Purchase Decision Kamera Filmonkish pada Generasi Z dengan Perceived Vicarious Nostalgia sebagai Variabel Mediasi - Fittyanasarani, Viwi; Erna Listiana; Ana Fitriana; Ramadhania Ramadhania; Bintoro Bagus Purmono (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Fear of Missing Out (FOMO) and electronic word of mouth (e-WOM) on the purchase decisions of Filmonkish cameras, with Perceived Vicarious Nostalgia acting as a mediating variable among Generation Z consumers. The research applies a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with data collected from 116 respondents who use Filmonkish cameras. The findings reveal that e-WOM and Perceived Vicarious Nostalgia have a significant effect on purchase decisions, indicating that information shared online and nostalgic emotional responses play an important role in shaping consumer behavior. In contrast, FOMO does not show a significant influence on either perceived nostalgia or purchase decisions. Furthermore, Perceived Vicarious Nostalgia does not function as a mediating variable in the relationship between FOMO and purchase decisions. These results suggest that Generation Z consumers tend to base their decisions more on credible information and emotional nostalgia associated with retro photography rather than on social pressure to follow trends. The study also offers theoretical insights and practical implications for marketing strategies in the retro camera industry.